Analysis of The Effectiveness of Competency-Based Performance Assessment Systems in Companies in Cirebon Regency - Hanif, Afif Aqielul; Belhfandho, Nibroos; Nurdiana, Editya (Siber International Journal of Digital Business (SIJDB), 2025)
Competency-based performance appraisals have evolved as an alternative to traditional appraisal systems that focus more on quantitative achievement. This study aims to analyze the effectiveness of the implementation of a competency-based performance appraisal system in companies in Cirebon Regency. With a quantitative approach and a descriptive research design, this study examines the relationship between the application of competency-based systems and individual and organizational performance using descriptive and inferential statistical analysis.  The results showed that most respondents (75%) felt that competency-based systems were fairer and provided a more comprehensive picture of employee performance compared to traditional quantitative-based systems. The results of the linear regression test showed a significant positive relationship between the implementation of the competency-based assessment system and employee performance (R² = 0.68, p < 0.05). This indicates that the more effectively this system is implemented, the higher the level of employee satisfaction and productivity. However, the main challenge in implementing this system is the lack of a clear understanding of the competencies assessed and the mismatch between the competency indicators used and the needs of the company. In addition, transparency and consistency in the implementation of the system were also found to be important factors that affect the effectiveness of the system. This study recommends strategic steps to improve the effectiveness of competency-based assessment systems, including through increased socialization and training for employees and managers, as well as the development of clearer and measurable competency indicators. Thus, a competency-based assessment system can have a more positive impact on improving individual performance, work motivation, and organizational productivity in Cirebon Regency companies.